Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 1414 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Tithonia diversifolia (Hemsl.) A.Gray" ] } The dataset includes 1414 records from 98 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0002842-150422101436696/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences